2002
DOI: 10.1021/jp0256589
|View full text |Cite
|
Sign up to set email alerts
|

Unoccupied States in C60 Thin Films Probed by Two-Photon Photoemission

Abstract: Unoccupied electronic states in C 60 thin films on Cu(111) have been measured by laser two-photon photoemission (2PPE) spectroscopy. These measurements allow the quantitative determination of energetic positions for the lowest unoccupied molecular orbital (LUMO), LUMO + 1, LUMO + 2, image potential states, as well as the highest occupied molecular orbital (HOMO). The transiently populated LUMO and LUMO + 1 levels are stabilized by the on-molecule charge correlation energy during the 2PPE process. Compared to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
69
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(79 citation statements)
references
References 31 publications
10
69
0
Order By: Relevance
“…The Hubbard U of fullerite can be estimated to U = 0.8 eV from the conduction band gap and the lowest exciton energy. Zhu and coworkers [74] showed that going from 20 to 2 ML fullerite on Cu(111) U decreases to 0.3 eV, which is in agreement with figure 2.7. In the surface layer U is 1.0 eV [40,100].…”
Section: Electrostatic Effectssupporting
confidence: 81%
See 1 more Smart Citation
“…The Hubbard U of fullerite can be estimated to U = 0.8 eV from the conduction band gap and the lowest exciton energy. Zhu and coworkers [74] showed that going from 20 to 2 ML fullerite on Cu(111) U decreases to 0.3 eV, which is in agreement with figure 2.7. In the surface layer U is 1.0 eV [40,100].…”
Section: Electrostatic Effectssupporting
confidence: 81%
“…Integration of the charge redistribution yields the net charge transfer into C 60 as a function of the definition of the precise position of the interface between Cu(111) and C 60 . The range of values of this integral explains the range of the reported charge transfers which is 0.8 [73] to 2.0 [74] electrons per C 60 molecule. Eberhardt and coworkers [38] observed the LUMO+1, the LUMO and the singlet exciton in a 3 nm thick fullerite film on Ag(100).…”
Section: Thin Films On Cu(111)mentioning
confidence: 79%
“…This is in contradiction with the monolayer structure typically found for annealing at higher temperature. 8,9,[11][12][13][14][15][16][17][18][19][20] It could well be that the alternating azimuthal orientations correspond to the two alternating binding sites that we have found for the isolated C 60 molecules on Cu͑111͒. The preferred spacing of the fullerenes in a monolayer could favor an alternating pattern of binding-site occupations that are also associated with different preferred azimuthal orientations.…”
Section: Ontop͑ii͒mentioning
confidence: 64%
“…This is in full agreement with the ͑4 ϫ 4͒ structure found in many previous studies after annealing. 8,9,[11][12][13][14][15][16][17][18][19][20] The annealed films show an increased number of substrate steps underneath the C 60 film-an indication that the annealing induces a surface reconstruction of the Cu͑111͒ surface. 23 We therefore believe that the resulting geometry is in this case not related to the monomer experiments.…”
Section: Ontop͑ii͒mentioning
confidence: 98%
See 1 more Smart Citation